2015
DOI: 10.1159/000437432
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Dependence and Genetic Variability in the Serotonin Pathway among Currently and Formerly Alcohol-Dependent Males

Abstract: Background: Genes involved in the serotonin pathway may determine the susceptibility to alcohol dependence and its severity. The present study explored whether specific polymorphisms in the serotonin pathway could be associated with alcohol dependence or alcohol-related psychopathological symptoms. Methods: The cohort comprised 101 currently and 100 formerly alcohol-dependent males, as well as 97 male healthy blood donors. The following questionnaires were employed: the Alcohol Use Disorders Identification Tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…Only few studies investigated the association of rs13212041 HTR1B gene polymorphism with alcohol dependence,41,42 but not with early- and late-onset alcoholism subtypes. This transition substitution (A1997G) in the distal 3′-untranslational region (UTR) of HTR1B messenger RNA disrupts a binding site for the microRNA, miR-96 40.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only few studies investigated the association of rs13212041 HTR1B gene polymorphism with alcohol dependence,41,42 but not with early- and late-onset alcoholism subtypes. This transition substitution (A1997G) in the distal 3′-untranslational region (UTR) of HTR1B messenger RNA disrupts a binding site for the microRNA, miR-96 40.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, other authors failed to confirm these findings,3739 perhaps due to the variability of alcohol-dependent phenotypes. However, only few studies investigated rs13212041 polymorphism, shown to modulate HTRIB gene expression,40 and its role in alcohol dependence 41,42…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have identified a number of single nucleotide polymorphisms that are associated with alcohol dependence and/or drug codependence including (a) CHRM2 (Luo et al, 2005; Wang et al, 2004), CHRNA4 (Kim et al, 2004), CHRNA5 (Saccone et al, 2007; Wang et al, 2009) as well as the CHRNA5-CHRNA3-CHRNB4 cluster and alcohol abuse/dependence (Schlaepfer et al, 2008); (b) DAT (Heinz, Goldman, Gallinat, Schumann, & Puls, 2004; see also Bhaskar & Kumar, 2014 for this and other DA-associated polymorphisms), DA beta hydroxylase (DBH) and alcohol dependence in women (Preuss et al, 2013), DRD3 and alcohol craving (Agrawal et al, 2013) as well as DA dysfunction and Cloninger Type I alcoholism (Leggio & Addolorato, 2008); (c) GABRA1, GABRA2, GABRB3, GABRG3 and alcohol dependence or sensitivity to its intoxicating effects during the ascending slope of the BAC curve (e.g., Bierut et al, 2010; Dick et al, 2004; Dick et al, 2006; Edenberg et al, 2004; Enoch, Schwartz, Albaugh, Virkkunen, & Goldman, 2006; Haughey et al, 2008; Noble et al, 1998); (d) GRIK3 (Grzywacz, Malecka, Suchanecka, Bienkowski, Samochowiec, 2013) and GRIN2A (Domart et al, 2012) with alcohol dependence as well as GRM8 and event-related potential (ERP) theta power and alcohol dependence (Chen et al, 2009); (e) 5HT dysfunction and Cloninger Type II alcoholism (Leggio & Addolorato, 2008), HTR1A and alcohol as well as nicotine co-dependence (Zuo et al, 2013), HTR1B and alcohol as well as multiple drug abuse (Cao, LaRocque, & Li, 2013; Contini et al, 2012), HTR2A and alcohol as well as heroin abuse (Cao et al, 2014), HTR7 and alcohol dependence as wel as electrophysiological measures (Zlojutro et al, 2010; Zuo et al, 2014), alcohol dependence and SERT (e.g., Heinz et al, 2004; c.f., Johnson, 2010; McHugh, Hofman, Asnaani, Sawyer, & Otto, 2010; Plemenitas et al, 2015); (f) OPRM1 and level of response to ethanol in Native Americans (Ehlers, Lind, & Wilhelmsen, 2008), OPRM1 polymorphisms and naltrexone’s efficacy for treating alcohol dependence (e.g., Jonas et al, 2014), as well as PDYN and OPRK1 with alcohol dependence (Gerra et al, 2007; Williams et al, 2007; Xuei et al, 2006); (g) CRFR1 polymorphism with P3 ERP and alcohol dependence (Chen et al, 2010); and (h) NPY and its receptor’s association with alcohol as well as multiple drug abuse and dependencies (Bhaskar et al, 2013; Frances et al, 2011; Okahisa et al, 2009; Sato et al, 2010; Wether...…”
Section: Pharmacogenomics and Alcoholism/addictionmentioning
confidence: 99%
“…Previous genetic studies on alcoholism suggested the existence of functional variants of selected genes that influence drinking behavior and are risk factors for alcohol dependence (Hallikainen et al, 1999, Wojnar et al, 2009, Wang et al, 2011, Bach et al, 2015, Plemenitas et al, 2015). It is known that the neurobiology of alcoholism involves alterations in neurotransmitter systems, e.g., the dopaminergic system (Gilpin and Koob, 2008, Karkhanis et al, 2015, Vasconcelos et al, 2015).…”
Section: 1 Introductionmentioning
confidence: 99%